Magnitude of Anemia and Its Associated Factors Among Pregnant Women Attending Antenatal Care in Southern Ethiopia: A Cross-Sectional Study - Argaw, Dirshaye (J Blood Med, 2020)
PURPOSE: The aim of this study was to assess the magnitude of anemia and its associated factors among pregnant women attending antenatal care (ANC) at Dilla University referral Hospital, South Ethiopia. PATIENTS AND METHODS: An institution-based cross-sectional study was conducted from January to February 2019, among 373 pregnant women who attended antenatal care at Dilla University referral hospital. Socio-demographic factors, nutritional, medical and obstetric information of the study participants were collected using a structured questionnaire. Hemoglobin was measured using a hemacue machine, and fecal specimens were examined to detect intestinal parasites. Bivariate and multiple variable binary logistic regressions were used to identify predictors of anemia. A p-value less than 0.05 was used to declare statistical significance. RESULTS: Overall prevalence of anemia was 28.7%, of which 19.6% had mild anemia. Decreased odds of anemia were found in women with good nutritional status (MUAC ≥24 cm) (AOR= 0.07 95% CI: 0.03–0.1), iron supplementation (AOR=0.06 95% CI: 0.02–0.15) and birth spacing ≥2 yrs (AOR=0.03 95% CI: 0.009–0.45). However, increased odds of anemia were seen in pregnant women with intestinal parasites (AOR=6.11 95% CI 7.70–37.0). CONCLUSION: The magnitude of anemia among pregnant women was found to be a moderate public health problem. Iron supplementation, good nutritional status (MUAC> 24 cm), and birth spacing reduce the odds of anemia. But having intestinal parasites was found to increase the likelihood of anemia during pregnancy. Counseling on birth spacing, strengthening iron supplementation, and intestinal parasite management during pregnancy should be given due emphasis.